Patients' strategies to deal with their situation at an emergency department. Issue 1 (20th April 2014) - Elmqvist, Carina; Frank, Catharina
<x xml:space="preserve">Abstract</x> Introduction The care in the emergency department (ED) is often characterised by high standards of efficiency and rapid treatment and the encounter between patient and staff can be described as both short and fragmented. Research within this field has mostly been performed with quantitative measurements and patients are both satisfied and vulnerable in their care at an ED. There is a lack of qualitative studies about patient's strategies to deal with their situation. Aim The aim was to describe patient's strategies for dealing with their situation at an ED. Methods Secondary analysis has been made of 13 qualitative interviews grounded in a lifeworld perspective. The interviews were analysed by qualitative content analysis. Results The results showed that patients' strategies to deal with the situation at the ED are passive or active. The passive strategy is being patient and the active strategies varied in terms of having hidden tactics, using visible tactics and using families as support. Conclusion These findings increase the importance of gaining knowledge about these strategies so that the staff at the ED can support the patients so they do not have to use them.